PENGARUH MARKET VALUE ADDED (MVA) DAN RASIO PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Desi Permata Sari; Zufrizal Harahap; Farida Khairani Lubis; Shofwan Andri (Universitas Islam Islam Sumatera Utara, 2021)
This study aims to determine the effect of market value added,and profitability ratios, on firm value partially and simultaneously in building construction sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The population in this study were 56 companies and the samples in this study were 19 manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 3 years to 57. This study uses secondary data. The data collected is data from manufacturing sector companies listed on the Indonesia Stock Exchange.Data analysis using multiple linear regression. The results showed that market value added had a positive dan significant effect on price to book value, return on equity had a positive and significant effect on price to book value and jointly the market value added and return on equity variables had a positive and significant effect on price to book value.”